Mark R. Johnson, creator of Ultima Ratio Regum: Interview - Knoll, Tobias (Online - Heidelberg journal of religions on the internet, 2016)
For our third special issue on religion and digital games, Online had a chat with Mark R Johnson, games studies scholar at the University of York and creator of Ultima Ratio Regum1, an ambitious game project aiming at creating “the most culturally, religiously and socially detailed proceduralworld ever generated.”